Tuberculosis of Sacrum: A Rare Location of Spinal Tuberculosis - Sinaga, Patrice LWY; Ibrahim, Sabri; Dharmajaya, Ridha (Asian Australasian Neuro and Health Science Journal (AANHS-J), 2019)
Abstract :Tuberculosis is one of the most common infectious diseases in the world. The thoracolumbar spine is the commonest form of vertebral tuberculosis, whereas isolated tuberculosis of the sacrum is rarely reported in the literature. A male patient of 22-year old had complained low back pain since 2 years before admission to hospital without history of trauma on back. He also got low-grade fever and weight loss. There was no tuberculosis contagion found, no cough or night sweat. Clinical examination revealed neurological deficit with strength of both lower extremities were 4 and hipestesia in the level of lumbal 5 and downward. Radiographs of lumbosacral showed deformity of lumbal 5. CT scans of spine showed deformity of sacrum. MRI revealed spondylolisthesis L5-S1, S1-S2, S2-S3 and mass in the anterior posterior and lateral of paralumbal 5 and parasacral. There is no involvement of gluteus muscle and the around muscle. The patient underwent surgical of sequestrectomy with drainage abscess and lumbo-sacral-illiac fusion. The culture of sacral tissue showed Mycobacterium tuberculosis. The patient was treated with combination of four antituberculosis agents.